A brief submaximal isometric exercise test 'unmasks' systolic and diastolic masked hypertension. Issue 4 (April 2019) - Koletsos, Nikolaos; Dipla, Konstantina; Triantafyllou, Areti; Gkaliagkousi, Eugenia; Sachpekidis, Vasileios; Zafeiridis, Andreas; Douma, Stella
Abstract : Objectives: An exaggerated blood pressure (BP) response during dynamic exercise testing has been proposed as an additional screening tool to identify systolic masked hypertension (masked-HYP). However, masked-HYP in young people is often characterized by an elevated DBP. Static/isometric exercise elicits augmented sympathetic stimulation causing greater increases in both SBP and DBP than dynamic exercise. Aims: To examine whether individuals with masked-HYP exhibit exaggerated BP responses during a submaximal handgrip vs. normotensive individuals and individuals with sustained hypertension (true-HYP), and the possible associations of exercise BP with total peripheral resistance (TPR), central/aortic BP, and 24-h-ambulatory BP (24-h BP). Methods: Eighty-six participants [untreated, newly diagnosed, masked-HYP ( n  = 27), true-HYP ( n  = 31), and normotensive individuals ( n  = 28); 46.3 ± 10.7 years], following evaluation of office BP, central/aortic BP, pulse wave velocity, carotid intima–media thickness, echocardiocardiography, and 24-h BP, underwent a 3-min handgrip (30% maximal voluntary contraction) with beat-by-beat BP and hemodynamics assessment (Finapres Medical Systems). Results: Despite similar baseline-BP in masked-HYP and normotensive individuals, during exercise masked-HYP exhibited a markedly greater ( P  < 0.01) SBP and DBP vs. normotensive individuals, and similar BP to true-HYP. TPR significantly increased ( P  < 0.001) during exercise, in masked-HYP and true-HYP. The exaggerated BP responses in masked-HYP were evident from the 1st minute of exercise and correlated ( P  < 0.05) with central/aortic-BP, aortic stiffness, 24-h BP, day-BP, night-time-BP, and interventricular septum thickness. Conclusion: During handgrip, masked-HYP exhibited exaggerated BP and TPR responses, similar to those of true-HYP. These responses were evident from the 1st minute of exercise and correlated with 24-h BP, suggesting that systolic and diastolic masked-HYP can be 'unmasked' during a brief, submaximal, handgrip test.